1991
DOI: 10.1093/ee/20.3.841
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Eggs of Colorado Potato Beetle (Coleoptera: Chrysomelidae) from Predation by Coleomegilla maculata (Coleoptera: Coccinellidae)

Abstract: Mortality to the egg stage of Colorado potato beetle, Leptinotarsa decemlineata(Say), from endemic predators was assessed in unsprayed plots within commercial potato fields in western Massacusetts in 1986 and 1987. Direct measurement of recruitment into the egg stage and of lossesto predation gave estimates of total stage-specific mortality for each generation of Colorado potato beetle and daily mortality rates. Abundance of endemic egg predators was measured through direct observation and trapping. Coleomegil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 10 publications
2
38
0
Order By: Relevance
“…Generalist predators have been shown to contribute to biological control of several potato pests. For example, predatory ladybird beetles can be effective predators of Colorado potato beetle eggs (Hazzard et al 1991, Nault and Kennedy 2000, Snyder and Clevenger 2004, and predatory stinkbugs have been examined for augmentative biocontrol of beetle larvae (HoughGoldstein and Keil 1991, Biever and Chauvin 1992, Cloutier and Jean 1998, Tipping et al 1999. While single predator taxa can, at times, have a strong impact, there is growing evidence that diverse guilds may be more effective (Walsh and Riley 1868, Tamaki and Weeks 1972a, Ferguson and Chapman 1993, HoughGoldstein et al 1993, Stoner 1993, Brust 1994.…”
mentioning
confidence: 99%
“…Generalist predators have been shown to contribute to biological control of several potato pests. For example, predatory ladybird beetles can be effective predators of Colorado potato beetle eggs (Hazzard et al 1991, Nault and Kennedy 2000, Snyder and Clevenger 2004, and predatory stinkbugs have been examined for augmentative biocontrol of beetle larvae (HoughGoldstein and Keil 1991, Biever and Chauvin 1992, Cloutier and Jean 1998, Tipping et al 1999. While single predator taxa can, at times, have a strong impact, there is growing evidence that diverse guilds may be more effective (Walsh and Riley 1868, Tamaki and Weeks 1972a, Ferguson and Chapman 1993, HoughGoldstein et al 1993, Stoner 1993, Brust 1994.…”
mentioning
confidence: 99%
“…(1997) used 6–7 C. maculata adults per plant in their field studies compared to the density of one ladybeetle per plant used in our study. The density we employed was at the upper end of those observed in other studies of C. maculata densities in commercial potato fields (Hazzard et al., 1991; Hilbeck et al., 1997). This difference in predator densities may have influenced the prey consumption observed in each study, by changing the type and frequency of behavioral interactions between individual predators.…”
Section: Discussionmentioning
confidence: 99%
“…These insects occur frequently in potato crops (Mack & Smilowitz, 1978; Obrycki & Tauber, 1985; Nault & Kennedy, 1996), and are apparently immune to the toxic effects of the Bt endotoxin expressed by CPB‐resistant Bt‐potatoes (Hofte & Whiteley, 1989; Hruska & Pavon, 1997). In addition to incorporating greater realism by adding prey choice for the predator involved, this study used a density of C. maculata within the range reported to co‐occur most often with CPB populations in potato in the eastern USA (Groden et al., 1990; Hazzard et al., 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Entomological research has shown this to be a sound strategy in many cases, contributing toward the control of such pests as apple blotch leafminer (Van Driesche and Taub, 1983), Colorado potato beetle (Hazzard et al, 1990), two-spotted spider mite (Prokopy et al, 1990), and European corn borer (Coll and Botrell, unpublished data). This approach to pest control is a form of biological control and is referred to as natural enemy conservation.…”
Section: Volume 4 Numbers 3 and 4 1989mentioning
confidence: 99%